Subvisible (2–100 μm) Particle Analysis During Biotherapeutic Drug Product Development: Part 1, Considerations and Strategy. Issue 6 (1st April 2015) - Narhi, Linda O.; Corvari, Vincent; Ripple, Dean C.; Afonina, Nataliya; Cecchini, Irene; Defelippis, Michael R.; Garidel, Patrick; Herre, Andrea; Koulov, Atanas V.; Lubiniecki, Tony; Mahler, Hanns‐Christian; Mangiagalli, Paolo; et al.
<x xml:space="preserve">Abstract</x> Measurement and characterization of subvisible particles (defined here as those ranging in size from 2 to 100 μm), including proteinaceous and nonproteinaceous particles, is an important part of every stage of protein therapeutic development. The tools used and the ways in which the information generated is applied depends on the particular product development stage, the amount of material, and the time available for the analysis. In order to compare results across laboratories and products, it is important to harmonize nomenclature, experimental protocols, data analysis, and interpretation. In this manuscript on perspectives on subvisible particles in protein therapeutic drug products, we focus on the tools available for detection, characterization, and quantification of these species and the strategy around their application. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1899–1908, 2015